Ni/NiO Based 3D Core-Shell Foam Anode for Lithium Ion Batteries. (20th October 2015) - Kvasha, Andriy; Azaceta, Eneko; Leonet, Olatz; Bengoechea, Miguel; Boyano, Iker; Tena-Zaera, Ramón; Meatza, Iratxe de; Miguel, Oscar; Grande, Hans-Jurgen; Blazquez, J. Alberto
Highlights: Ni/NiO anodes are processed by electrodeposition NiO from ionic liquids Annealed Ni/NiO-electrode provides enhanced specific capacity and stable cyclability NiO sub-layer, formed by thermal oxidation, is the main origin of capacity increase Electrochemical performance of Ni/NiO anodes was evaluated in half and full cells Abstract: An innovative route to obtain Ni/NiO core-shell foam-based anodes for lithium-ion batteries is presented. Commercial Ni foams are conformally coated with NiO by ionic liquid-based electrodeposition. The electrochemical behavior of the resulting Ni/NiO electrodes in half coin cells with lithium counter electrode is investigated. The results are qualitatively correlated to the microstructural properties, including effects of the thermal annealing at 500 °C, of the NiO shell. The formation a NiO sub-layer by the thermal oxidation of the Ni foam seems to play a crucial role in the enhanced performance of the annealed Ni/NiO anodes, which exhibit a reversible discharge capacity around 0.8 mAh/cm 2 . Furthermore, the Ni/NiO core-shell foam-based anodes are evaluated in full coin Li-ion cells with high voltage LiMn0.8 Fe0.2 PO4 cathode. Promising cyclability is reached in NiO-LMFP coin cells under cycling at 0.4C.